2015
DOI: 10.1002/jmrs.144
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of hepatic oligometastases with stereotactic ablative radiotherapy and radiofrequency ablation in an anaplastic lymphoma kinase fusion‐positive lung cancer patient

Abstract: Local ablative therapy with stereotactic ablative radiotherapy may improve survival in oncogene‐addicted lung cancer patients with extracranial oligometastatic disease treated with targeted therapies. There is limited data on the use of radiofrequency ablation (RFA) in this same setting. We present a case of an anaplastic lymphoma kinase (ALK)‐positive lung cancer patient with hepatic oligometastatic progression who was successfully treated with both stereotactic ablative radiation and RFA while continuing wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…First of all, while FISH and IHC detect relatively indirect signs of the presence of ALK translocation, RT‐PCR usually reveals the exact variant of the rearrangement and therefore provides definitive evidence of ALK fusion. Furthermore, RT‐PCR has high sensitivity and specificity, with a rapid turnaround time and ease of analysis, and can detect a small number (1%) of ALK ‐driven NSCLC cells in the presence of normal tissues . In addition, RT‐PCR analysis utilizes the same technical platform as other kinds of molecular NSCLC diagnosis, for example EGFR testing.…”
Section: Alk Rearrangement Detection Methods In Nsclc Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, while FISH and IHC detect relatively indirect signs of the presence of ALK translocation, RT‐PCR usually reveals the exact variant of the rearrangement and therefore provides definitive evidence of ALK fusion. Furthermore, RT‐PCR has high sensitivity and specificity, with a rapid turnaround time and ease of analysis, and can detect a small number (1%) of ALK ‐driven NSCLC cells in the presence of normal tissues . In addition, RT‐PCR analysis utilizes the same technical platform as other kinds of molecular NSCLC diagnosis, for example EGFR testing.…”
Section: Alk Rearrangement Detection Methods In Nsclc Patientsmentioning
confidence: 99%
“…Furthermore, RT-PCR has high sensitivity and specificity, with a rapid turnaround time and ease of analysis, and can detect a small number (1%) of ALK-driven NSCLC cells in the presence of normal tissues. [64][65][66] In addition, RT-PCR analysis utilizes the same technical platform as other kinds of molecular NSCLC diagnosis, for example EGFR testing. Finally, a number of commercial RT-PCR kits for detection of ALK rearrangements have been developed recently, including: the ALK RGQ RT-PCR Kit (Qiagen, Valencia, CA, USA); the EML4-ALK Fusion Gene Detection Kit (Amoy Diagnostics, Xiamen, China); and EML4 ALK Gene Fusion, PCR (Quest Diagnostics, Secaucus, NJ, USA).…”
Section: Types Of Oncogenesis In Alkmentioning
confidence: 99%
“…Recently, a case report of a patient with ALKpositive NSCLC whose disease progressed during administration of both crizotinib and ceritinib and in whom a new hepatic metastatic lesion developed showed that RFA can be effectively used to treat oligoprogressive NSCLC. 75 Limitations of Available Data. Despite evidence supporting the use of LAT for oligoprogressive NSCLC, the aforementioned studies need to be interpreted with caution.…”
Section: Use Of Lat For Oligoprogressive Diseasementioning
confidence: 99%
“…However, recent studies using FISH and IHC or FISH alone in comparison to RT-PCR have demonstrated that RT-PCR has a high sensitivity and specificity [ 14 , 15 , 16 ]. These tests have the advantages of a rapid turn-around time and ease of analysis, and can be used on biopsy or cytology specimens with lower tumor content than needed for accurate FISH and IHC testing [ 14 , 15 , 17 ]. In the study described in this report, we compare a commercially available RT-PCR assay (ALK RGQ RT-PCR Kit, QIAGEN, Manchester, UK) designed to identify mRNA produced by all ALK rearrangements regardless of the fusion partner or variant ( Figure 1 ), with IHC that detects the ALK protein and FISH that directly identifies ALK genomic rearrangements in FFPE samples from patients with NSCLC.…”
Section: Introductionmentioning
confidence: 99%